Effectiveness of podal reflexology in patients with cervical osteoarthritis - Marbelis Barthelemy Velázquez; Joaquín Maturell Lorenzo; Ernesto Sánchez Hernández; Bertha Ileana Torres Reyes (Centro Provincial de Información de Ciencias Médicas, 2017)
A therapeutic intervention in 118 patients with cervical osteoarthritis was carried out. They were assisted in the Comprehensive Rehabilitation Service of "Dr. Joaquín Castillo Duany" Teaching Clinical Surgical Hospital in Santiago de Cuba, from July, 2013 to December, 2014, to evaluate the effectiveness of podal reflexology as a treatment modality. The sample was divided in 2 groups (study group and control group), of 54 members each, paired by age and sex. In both groups, the highest number of affected patients were over 50 years; also, a little more than two thirds of the selected individuals improved at 7 days of the clinical course and with only 3 treatment sessions, until the definitive resolution at 21 days (9 sessions).  An adverse effect was registered and it was concluded that this therapy guarantees a significant improvement of symptoms, so its high effectiveness, without excessive consumption of time.